Acute toxicity of Neonicotinoids and Carbamete on Honey Bee Apis mellifera L - Hassan Tarek; Ali S. Moalif; Ernesto Guzman (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Objectives: The current study represents the first part of a Ph.D. research projectconducted at The University of Guelph, Ontario, Canada in co-operation with the University of Babylon,Hilla – Iraq. The main objective of this part was to estimate the acute toxicity (LD 50) of clothianidin,imidacloprid (neonicotinoids), and carbaryl (Crabmeat) to honey bees. Method: The Three insecticides havebeen blamed for the colony collapse disorder (CCD) crisis, newly emerged adult bees were challenged orallyand topically with a serial of doses of the three insecticides. Determination of the LD50 of each insecticiderevealed that clothianidin was the most toxic insecticide to bees in oral and topical applications comparedto the other two insecticides. The findings: The oral LD50 values were 0.004, 0.15, and 0.36 forclothianidin, imidacloprid, and carbaryl respectively. The topical LD50 values were 0.034, 0.085, and 0.24for the three insecticides respectively Data were statistically analyzed by probit analysis using theUS Environmental protection Agency statistical program (version 1-5).